Design of a Rotating Drum for Electrospinning Setup with Adjustable Speed - Koh, Ching Theng; Ham Wen Jun, (Research Progress in Mechanical and Manufacturing Engineering, 2020)
This study is aimed to design a rotating collector drum to collect a large surface area of aligned polymeric fibers. There are some parameters that affect the degree of fibers alignment such as type of collector, speed of rotating drum, voltage, distance between syringe tip and collector, polymer concentration and feed rate. Collector drum having 80 mm diameter is selected to collect large surface area of fibers. Stainless steel is selected as the material of collector drum due to its resistance to corrosion in extreme acidic environments. In order to adjust the rotation speed of collector drum, AC motor is chosen as it uses electromagnetic induction to power the rotating device such as shaft. The safety, stability and suitability of rotating drum for large speed (>3000 rpm) were considered during the design.  The rotating drum design in this project allows the production of nanofibers with controllable alignment.